Multi-phase doped high-conductivity tungsten-copper composite material and preparation method and application thereof
By plating Co film on the surface of graphene and copper powder and adopting thermal isostatic sintering technology, the problem of difficult to take into account both the thermal conductivity and mechanical properties of tungsten copper composite materials is solved, and a tungsten copper composite material with high density and excellent thermal conductivity is achieved.
Patent Information
- Application Number
- CN202411901720.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing tungsten-copper composite materials are difficult to take into account both the conductivity and the mechanical properties, and the wettability between tungsten and copper is poor, resulting in poor density and mechanical properties.
Co films are coated on the surface of graphene and copper powder by magnetron sputtering to optimize the wettability between tungsten and copper, and a multiphase doped tungsten copper composite material is prepared by thermal isostatic sintering technology.
It significantly improves the density and mechanical properties of tungsten copper composite materials, while also having excellent electrical conductivity and thermal conductivity, achieving a good balance between conductive thermal conductivity and mechanical properties.
Smart Images

Figure CN119753405A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of tungsten-copper composite materials, and specifically relates to a multi-phase doped high-conductivity tungsten-copper composite material and a preparation method and application thereof. Background Art
[0002] Tungsten copper alloy is an alloy composed of tungsten (W) and copper (Cu). It combines the high melting point and high strength of tungsten with the electrical conductivity and thermal conductivity of copper, and is used in electronic packaging, thermal deposition and high-voltage electrical contact materials. However, the properties of W and Cu are quite different, and they are difficult to dissolve in each other and have poor wettability, so it is difficult to obtain a high-density tungsten copper alloy. To solve this problem, the existing technology mainly improves the wettability between W and Cu by doping transition elements (Pd, Ni, Co), rare earth metal elements (La, Ce), ceramic phases (TiC, TiB, Al2O3), etc. to improve the mechanical properties, but the electrical and thermal conductivity will decrease. Graphene has a high Young's modulus (1100GPa), strength (130GPa), thermal conductivity (5000W / mK), carrier migration efficiency (15000cm 2 / (v·s)), which can be used as a reinforcing phase of the composite material to improve thermal and electrical conductivity. However, on the one hand, WC is easily formed between graphene and W under high-temperature sintering, and heat may be scattered at the interface between WC and the copper-tungsten matrix during the transfer process, resulting in reduced thermal conduction efficiency. On the other hand, graphene has a small density and is easy to agglomerate. It is difficult to evenly disperse graphene into the tungsten-copper alloy using traditional powder mixing methods. Therefore, the present invention combines the advantages of graphene and cobalt to prepare a tungsten-copper alloy with excellent comprehensive properties such as thermal conductivity, electrical conductivity, and high density. Summary of the invention
[0003] The purpose of the present invention is to solve the technical problems that the existing tungsten-copper composite materials have poor wettability of W and Cu and are difficult to balance mechanical properties and electrical properties, and to provide a multi-phase doped high-conductivity tungsten-copper composite material and its preparation method and application.
[0004] One of the purposes of the present invention is to provide a method for preparing a multi-phase doped high-conductivity tungsten-copper composite material, the method being carried out according to the following steps:
[0005] S1: Co is deposited on the surface of graphene powder and Cu powder by magnetron sputtering to obtain MLG@Co powder and Cu@Co powder respectively;
[0006] S2: MLG@Co powder, Cu@Co powder and tungsten powder are ball-milled and mixed, and sintered by hot isostatic pressing to obtain a multi-phase doped tungsten-copper composite material.
[0007] It is further defined that the graphene powder and Cu powder in S1 are first cleaned with acetone and ethanol solutions assisted by ultrasound to remove grease and oxide layer on the surface of the graphene powder and Cu powder before use.
[0008] It is further defined that the parameters for coating Co on the surface of graphene powder in S1 are: working gas pressure of 1 to 2 Pa, bias voltage of -100 V to -200 V, Co target power of 100 to 150 W, and time of 1 to 3 h.
[0009] It is further defined that the thickness of the Co film on the surface of the graphene powder in S1 is 50 to 100 nm.
[0010] It is further defined that the parameters for coating Co on the surface of Cu powder in S1 are: working pressure of 1-2 Pa, temperature of 50-200° C., bias of -50 V to -100 V, Co target power of 50-90 W, and time of 1 to 3 h.
[0011] It is further defined that the thickness of the Co film on the surface of the Cu powder in S1 is 50 to 100 nm.
[0012] Further definition, before magnetron sputtering in S1, vacuum 5×10 -4 Pa, and then Ar gas is introduced, and the graphene powder and Cu powder are cleaned by Ar gas at a vibration frequency of 5 to 10 Hz and a sputtering power of 10 to 20 W.
[0013] It is further defined that the mass percentages of MLG@Co powder, Cu@Co powder and tungsten powder in S2 are 2-4%, 10-30% and 70-90%, respectively.
[0014] It is further defined that the ball-to-material ratio in ball milling in S2 is 10:1, the rotation speed is 200-400 r / min, and the ball milling time is 6-8 h.
[0015] It is further defined that the hot isostatic pressing pressure in S2 is 80-100 MPa, the sintering temperature is 1000-1200°C, and the holding time is 1-3 hours.
[0016] The second object of the present invention is to provide a high-conductivity tungsten-copper composite material prepared by the above method, wherein the composite material has an electrical conductivity of ≥35% IACS and a density of ≥97%.
[0017] The third object of the present invention is to provide a high-conductivity tungsten-copper composite material prepared by the above method for use as an electrical contact material and an electronic component heat dissipation material.
[0018] A fourth object of the present invention is to provide a plasma first wall, wherein the plasma first wall is made of the above-mentioned high-conductivity tungsten-copper composite material.
[0019] A fifth object of the present invention is to provide an application of the above-mentioned plasma first wall in the field of thermonuclear fusion.
[0020] The advantages of the present invention compared to the prior art are:
[0021] The present invention coats the graphene and Cu surfaces with Co films respectively, optimizes the wettability between tungsten and copper, significantly improves the density and mechanical properties of the W / Cu composite material, and simultaneously adjusts the ratio of MLG@Co, Cu@Co powder and tungsten powder to make the obtained W / Cu composite material have both excellent conductivity and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the SEM image of the ball-milled mixed powder in Example 1;
[0023] Figure 2 This is the microstructure of the W / Cu composite material in Example 1. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0025] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0026] Embodiment 1: The preparation method of the multi-phase doped high-conductivity W / Cu composite material of this embodiment comprises the following steps:
[0027] (1) Ultrasonic cleaning of graphene powder and Cu powder
[0028] Graphene powder (10-20 μm) and Cu powder (58-75 μm) were respectively washed with acetone solution for 20 min, deionized water for 5 min, then washed with ethanol solution for 20 min, and deionized water for 5 min to remove grease and part of the oxide layer on the surface of graphene powder and Cu powder.
[0029] (2) MLG@Co obtained by magnetron sputtering
[0030] The graphene powder in step (1) is placed in a vibrating tank of a powder PVD coating device and vacuumized to 5 × 10 -4 Pa, and then 40 sccm Ar gas was introduced, and the graphene powder was cleaned with Ar gas at a vibration frequency of 10 Hz and a sputtering power of 15 W.
[0031] The graphene powder was coated with a Co film with a working pressure of 1.5 Pa, a bias voltage of -100 V, a Co target power of 100 W, a time of 2 h, and a Co film thickness of 60 nm.
[0032] (3) Obtaining Cu@Co powder by magnetron sputtering
[0033] The copper powder of step (1) was placed in a vibrating tank of a powder PVD coating device and vacuumed to 5 × 10 -4 Pa, and then 40 sccm Ar gas was introduced, and the copper powder was cleaned with Ar gas at a vibration frequency of 10 Hz and a sputtering power of 15 W.
[0034] For the copper powder coated with Co film, the working gas pressure is 1.5 Pa, the temperature is 100°C, the bias voltage is -50 V, the Co target power is 60 W, the time is 1.5 h, and the Co film thickness is 50 nm.
[0035] (4) Ball milling
[0036] MLG@Co powder, Cu@Co powder and tungsten powder (20-30 μm) were ball-milled at mass percentages of 2%, 18% and 80%, respectively, with a ball-to-material ratio of 10:1, a rotation speed of 300 r / min and a ball-milling time of 8 h.
[0037] (5) Hot isostatic pressing
[0038] The powder obtained in (4) was sintered by hot isostatic pressing at a pressure of 100 MPa and a sintering temperature of 1100°C for 2 h.
[0039] The W / Cu composite material of this embodiment, MLG@Co and Cu@Co powders, on the one hand, avoid the formation of WC and improve the conductivity, and on the other hand, avoid direct contact between Cu and W, and further improve the wettability between tungsten and copper, thereby obtaining a W / Cu composite material with excellent performance. Figure 1 This is the SEM picture of the mixed powder after ball milling. Figure 2 This is the microstructure of the W / Cu composite material, with relatively uniform grain size and dense structure.
[0040] Embodiment 2: The preparation method of the multi-phase doped high-conductivity W / Cu composite material of this embodiment comprises the following steps:
[0041] (1) Ultrasonic cleaning of graphene powder and Cu powder
[0042] Graphene powder (10-20 μm) and Cu powder (58-75 μm) were respectively washed with acetone solution for 20 min, deionized water for 5 min, then washed with ethanol solution for 20 min, and deionized water for 5 min to remove grease and part of the oxide layer on the surface of graphene powder and Cu powder.
[0043] (2) MLG@Co obtained by magnetron sputtering
[0044] The graphene powder in step (1) is placed in a vibrating tank of a powder PVD coating device and vacuumized to 5 × 10 -4 Pa, and then 40 sccm Ar gas was introduced, and the graphene powder was cleaned with Ar gas at a vibration frequency of 10 Hz and a sputtering power of 15 W.
[0045] The graphene powder was coated with a Co film with a working pressure of 1.5 Pa, a bias voltage of -100 V, a Co target power of 100 W, a time of 2 h, and a Co film thickness of 60 nm.
[0046] (3) Obtaining Cu@Co powder by magnetron sputtering
[0047] The copper powder of step (1) was placed in a vibrating tank of a powder PVD coating device and vacuumed to 5 × 10 -4 Pa, and then 40 sccm Ar gas was introduced, and the copper powder was cleaned with Ar gas at a vibration frequency of 10 Hz and a sputtering power of 15 W.
[0048] For the copper powder coated with Co film, the working gas pressure is 1.5 Pa, the temperature is 100°C, the bias voltage is -50 V, the Co target power is 60 W, the time is 1.5 h, and the Co film thickness is 50 nm.
[0049] (4) Ball milling
[0050] MLG@Co powder, Cu@Co powder and tungsten powder (20-30 μm) were ball-milled at mass percentages of 3%, 17% and 80%, respectively, with a ball-to-material ratio of 10:1, a rotation speed of 300 r / min and a ball-milling time of 8 h.
[0051] (5) Hot isostatic pressing
[0052] The powder obtained in (4) was sintered by hot isostatic pressing at a pressure of 100 MPa and a sintering temperature of 1100°C for 2 h.
[0053] In the W / Cu composite material of this embodiment, the introduction of Co improves the wettability between tungsten and copper, promotes the sintering densification of the alloy, and makes the structure uniform and dense. At the same time, by changing the graphene addition content by 2%, the influence of the content on the performance of the W / Cu composite material is explored.
[0054] Embodiment 3: The preparation method of the multi-phase doped high-conductivity W / Cu composite material of this embodiment comprises the following steps:
[0055] (1) Ultrasonic cleaning of graphene powder and Cu powder
[0056] Graphene powder (10-20 μm) and Cu powder (58-75 μm) were respectively washed with acetone solution for 20 min, deionized water for 5 min, then washed with ethanol solution for 20 min, and deionized water for 5 min to remove grease and part of the oxide layer on the surface of graphene powder and Cu powder.
[0057] (2) MLG@Co obtained by magnetron sputtering
[0058] The graphene powder in step (1) is placed in a vibrating tank of a powder PVD coating device and vacuumized to 5 × 10 -4 Pa, and then 40 sccm Ar gas was introduced, and the graphene powder was cleaned with Ar gas at a vibration frequency of 10 Hz and a sputtering power of 15 W.
[0059] The graphene powder was coated with a Co film with a working pressure of 1.5 Pa, a bias voltage of -100 V, a Co target power of 100 W, a time of 2 h, and a Co film thickness of 60 nm.
[0060] (3) Obtaining Cu@Co powder by magnetron sputtering
[0061] The copper powder of step (1) was placed in a vibrating tank of a powder PVD coating device and vacuumed to 5 × 10 -4 Pa, and then 40 sccm Ar gas was introduced, and the copper powder was cleaned with Ar gas at a vibration frequency of 10 Hz and a sputtering power of 15 W.
[0062] For the copper powder coated with Co film, the working gas pressure is 1.5 Pa, the temperature is 100°C, the bias voltage is -50 V, the Co target power is 60 W, the time is 1.5 h, and the Co film thickness is 50 nm.
[0063] (4) Ball milling
[0064] MLG@Co powder, Cu@Co powder and tungsten powder (20-30 μm) were ball-milled at mass percentages of 4%, 16% and 80%, respectively, with a ball-to-material ratio of 10:1, a rotation speed of 300 r / min and a ball-milling time of 8 h.
[0065] (5) Hot isostatic pressing
[0066] The powder obtained in (4) was sintered by hot isostatic pressing at a pressure of 100 MPa and a sintering temperature of 1100°C for 2 h.
[0067] In the W / Cu composite material of this embodiment, the introduction of Co improves the wettability between tungsten and copper, which can promote the sintering densification of the alloy and make the structure uniform and dense. At the same time, by changing the graphene addition content by 3%, the influence of the content on the performance of the W / Cu composite material is explored.
[0068] Comparative Example 1: The preparation method of the W / Cu composite material of this embodiment includes the following steps:
[0069] (1) Ultrasonic cleaning of Cu powder
[0070] The Cu powder (58-75 μm) was washed with acetone solution for 20 min, deionized water for 5 min, ethanol solution for 20 min, and deionized water for 5 min to remove grease and part of the oxide layer on the surface of the Cu powder.
[0071] (2) Magnetron sputtering to obtain Cu@Co powder
[0072] The copper powder of step (1) was placed in a vibrating tank of a powder PVD coating device and vacuumed to 5 × 10 -4 Pa, and then 40 sccm Ar gas was introduced, and the copper powder was cleaned with Ar gas at a vibration frequency of 10 Hz and a sputtering power of 15 W.
[0073] For the copper powder coated with Co film, the working gas pressure is 1.5 Pa, the temperature is 100°C, the bias voltage is -50 V, the Co target power is 60 W, the time is 1.5 h, and the Co film thickness is 50 nm.
[0074] (3) Ball milling
[0075] Cu@Co powder and tungsten powder (20-30 μm) were ball-milled at a mass percentage of 20% and 80%, respectively, with a ball-to-material ratio of 10:1, a rotation speed of 300 r / min, and a ball-milling time of 8 h.
[0076] (4) Hot isostatic pressing
[0077] The powder obtained in (3) was sintered by hot isostatic pressing at a pressure of 100 MPa and a sintering temperature of 1100°C for 2 h.
[0078] In the W / Cu composite material of this embodiment, although the introduction of Co improves the wettability between tungsten and copper, it reduces the electrical conductivity and thermal conductivity of the tungsten-copper alloy.
[0079] Comparative Example 2: The preparation method of the W / Cu composite material of this comparative example comprises the following steps:
[0080] (1) Ball milling
[0081] Cu powder (58-75 μm) and tungsten powder (20-30 μm) were ball-milled at a mass percentage of 20% and 80%, respectively, with a ball-to-material ratio of 10:1, a rotation speed of 300 r / min, and a ball-milling time of 8 h.
[0082] (2) Hot isostatic pressing
[0083] The powder obtained in (1) was sintered by hot isostatic pressing at a pressure of 100 MPa and a sintering temperature of 1100°C for 2 h.
[0084] The density, thermal conductivity and hardness of the W / Cu composite materials obtained in Examples 1-3 and Comparative Examples 1-2 were tested, and the results are shown in Table 1.
[0085] Table 1 Properties of W / Cu composite materials
[0086]
[0087] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a multi-phase doped high-conductivity tungsten-copper composite material, characterized in that: The method: S1: Co is deposited on the surface of graphene powder and Cu powder by magnetron sputtering to obtain MLG@Co powder and Cu@Co powder respectively; S2: MLG@Co powder, Cu@Co powder and tungsten powder are ball-milled and mixed, and sintered by hot isostatic pressing to obtain a multi-phase doped tungsten-copper composite material.
2. The method according to claim 1, characterized in that It is further defined that the parameters for coating Co on the surface of graphene powder in S1 are: working gas pressure of 1 to 2 Pa, bias voltage of -100 V to -200 V, Co target power of 100 to 150 W, and time of 1 to 3 h.
3. The method according to claim 1, characterized in that The parameters for coating Co on the surface of Cu powder in S1 are: working pressure of 1-2 Pa, temperature of 50-200° C., bias of -50 V to -100 V, Co target power of 50-90 W, and time of 1 to 3 h.
4. The method according to claim 1, characterized in that: The thickness of the Co film on the surface of graphene powder in S1 is 50-100 nm, and the thickness of the Co film on the surface of Cu powder is 50-100 nm.
5. The method according to claim 1, characterized in that: The mass percentages of MLG@Co powder, Cu@Co powder and tungsten powder in S2 are 2-4%, 10-30% and 70-90% respectively.
6. The method according to claim 1, characterized in that The hot isostatic pressing pressure of S2 is 80-100 MPa, the sintering temperature is 1000-1200°C, and the holding time is 1-3 hours.
7. The high-conductivity tungsten-copper composite material prepared by the method according to any one of claims 1 to 6, characterized in that: The composite material has an electrical conductivity of ≥35% IACS and a density of ≥97%.
8. The high-conductivity tungsten-copper composite material according to claim 7 is used as an electrical contact material and a heat dissipation material for electronic components.
9. A plasma first wall, characterized in that: The plasma first wall is made of the high-conductivity tungsten-copper composite material according to claim 7.
10. Application of the plasma first wall according to claim 9 in the field of thermonuclear fusion.
Citation Information
Patent Citations
Low-temperature preparation method of high-performance tungsten copper composite material
CN103589884A
Preparing method for graphene and carbon nano tube composite porous electrode material
CN105256312A
Foam graphene skeleton reinforced copper-base composite material and preparation method thereof
CN105603248A
Method for preparing copper-tungsten alloy doped graphene
CN108893637A
Graphene reinforced copper-based composite electrical contact material and preparation method thereof
CN117265314A